A Professional Development Framework for Higher Education Science Faculty that Improves Student Learning. (19th May 2021) - Cormas, Peter C; Gould, Gregg; Nicholson, Louise; Fredrick, Kyle C; Doan, S Y
Abstract: A recent impetus for the transformation of undergraduate science instruction to improve student learning has prompted stakeholders to support professional development (PD) of higher education science faculty (instructors). In turn, stakeholders have created successful PD for instructors on the basis of research in K–12 teacher PD. However, there is no framework for PD of instructors that has been linked to student learning. The purpose of this literature review and theoretical work is to organize instructors' PD research within a sequential framework for K–12 PD that has been linked to student learning, to examine limited evidence of student learning yielded from the PD of instructors, to determine whether and to what extent the entire sequence of the framework has been evaluated in PD for instructors, and to use a ubiquitous form of PD known as learning communities as a practical example for how to design, implement, and evaluate PD with the framework.